Macrophage Subsets Within Granulomatous Intestinal Lesions in Bovine Paratuberculosis. (January 2017) - Fernández, M.; Benavides, J.; Castaño, P.; Elguezabal, N.; Fuertes, M.; Muñoz, M.; Royo, M.; Ferreras, M. C.; Pérez, V.
Animals infected with Mycobacterium avium subspecies paratuberculosis show a variety of granulomatous lesions that range from focal forms, seen in the subclinical stages, to diffuse lesions associated with clinical signs. The aim of this study was to phenotypically characterize the macrophages present in the different lesion types using immunohistochemical methods. Lesions from a total of 23 animals with bovine paratuberculosis, natural and experimental, were examined by immunohistochemistry. Antibodies against inducible nitric oxide synthase (iNOS), tumor necrosis factor α (TNF-α), CD163, interleukin 10 (IL-10), transforming growth factor β (TGF-β), major histocompatibility complex (MHC) class II, natural resistance-associated macrophage protein 1 (Nramp-1), calprotectin, Ki-67, CD68, lysozyme, and ionized calcium-binding adaptor molecule 1 (Iba-1) molecules were employed. Samples were scored semiquantitatively using a complete histological score (H-score), reflecting the staining intensity and the percentage of immunolabeled macrophages. Differences in the H-score were seen depending on the lesion type. In focal lesions, with none or few acid-fast bacilli (AFB), macrophages were polarized toward M1 phenotype, with high H-scores for iNOS and TNF-α. Diffuse multibacillary lesions showed M2 differentiation, with high expression of CD163, IL-10, and TGF-β as well as Nramp-1 and MHC class II antigens. Macrophages in diffuse paucibacillary forms showed high H-scores for iNOS but low ones for TNF-α. Diffuse lesions, either multibacillary or paucibacillary, showed high calprotectin and low Ki-67 expression, suggesting a progressive character, while focal forms, with low H-scores for these antigens, would be consistent with latency. Lysozyme and CD68 expression were related to the amount of AFB. H-score for Iba-1 antibody was similar among all types. The findings of this study provide insights into the polarization status of macrophages and lesion development in bovine paratuberculosis.